From Words to Action: The Role of Transformative Constitutionalism in Fostering Social Change - Shashank Shekhar,; Priyank Kumar Verma, (AG Volumes, 2026)
In the sphere of constitutional law, the concept of transformative constitutionalism has come up as a critical framework for creating meaningful social change. This chapter explains the intricate interplay between constitutional texts and their transformative potential to produce societal shifts. Through an in-depth study of landmark legal cases, scholarly perspectives, and real-world examples, this chapter explores how transformative constitutionalism goes beyond the conventional boundaries of jurisprudence to fill the gap between rhetoric and reality. By examining the mechanisms through which constitutional principles are used to address deeply entrenched inequalities and systemic injustices, this discussion offers a comprehensive exploration of how legal frameworks can serve as cause for societal progress. It further emphasizes the vital role of judicial activism, civil society engagement, and policy implementation in translating constitutional ideals into sensible transformations. By illuminating the dynamic interaction between law, society, and change, this chapter contributes to a deeper understanding of the power of transformative constitutionalism in shaping a more equitable and just future.